2015
DOI: 10.1007/s11033-015-3898-2
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note to: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis

Abstract: The Publisher and Editor retract this article in accordance with the recommendations of the Committee on Publica tion Ethics (COPE). After a thorough investigation we have strong reason to believe that the peer review process was compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Genetic associations in distinct populations have been described, although no reported association has been widely replicated . A meta‐analysis carried out in order to investigate the impact of the KIR genes on susceptibility to AS indicated that the KIR2DL1, KIR2DS4, KIR2DS5 and KIR3DS1 genes might be associated closely with susceptibility to AS . However, few association studies of candidate genes and clinical manifestations in AS have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic associations in distinct populations have been described, although no reported association has been widely replicated . A meta‐analysis carried out in order to investigate the impact of the KIR genes on susceptibility to AS indicated that the KIR2DL1, KIR2DS4, KIR2DS5 and KIR3DS1 genes might be associated closely with susceptibility to AS . However, few association studies of candidate genes and clinical manifestations in AS have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of observational data accounted for 49 out of 85 retractions. A detailed analysis of six retracted systematic reviews in the field of rheumatology ( Table 2 ) 26 27 28 29 30 31 suggested that methodological errors were responsible for 2 and compromised, possibly fabricated peer review process was the cause for retraction in 3. In the remaining 1, it was identified after publication that certain studies had been missed, therefore, the review was retracted and a corrected version republished.…”
Section: Systematic Reviews In Rheumatology and Retractionsmentioning
confidence: 99%
“…Editors must be careful, considering the aforementioned recent instances of peer review compromise by fraudulent methods, which led to retraction of numerous systematic reviews ( Table 2 ). 28 29 30 32 Based on limited evidence ( Fig. 2 ), it may be prudent to view systematic reviews from certain geographic regions with greater caution.…”
Section: Perspectives For Systematic Reviewsmentioning
confidence: 99%